Problematika Implementasi Kurikulum Merdeka PAK dalam Pendidikan Sekolah Menengah Atas - Herda Sitanggang; Ordekoria Saragih (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
The purpose of conducting research on the implementation of the PAK independent curriculum is to find out the problems in its implementation, teachers are the main implementers of this curriculum in the field. By understanding their perspectives and experiences, we can find the problems they face and what is needed for the successful implementation of the curriculum. The research method used is to use a qualitative method with a literature review approach, namely looking for sources that are considered relevant to be used as sources for writing. Based on the results obtained, there are several difficulties or problems in its implementation, for example one of them is the reduction in human resources in this case, namely educators, and other things. The Merdeka Belajar curriculum focuses on important material, is flexible for teachers and students, and is project and character-based. By increasing teacher understanding, increasing resources, increasing parental participation, and developing a more contextual curriculum, it is hoped that the quality of religious education can be improved.